2017
DOI: 10.1098/rsif.2017.0060
|View full text |Cite|
|
Sign up to set email alerts
|

Body-monitoring with photonic textiles: a reflective heartbeat sensor based on polymer optical fibres

Abstract: Knowledge of an individual's skin condition is important for pressure ulcer prevention. Detecting early changes in skin through perfusion, oxygen saturation values, and pressure on tissue and subsequent therapeutic intervention could increase patients' quality of life drastically. However, most existing sensing options create additional risk of ulcer development due to further pressure on and chafing of the skin. Here, as a first component, we present a flexible, photonic textile-based sensor for the continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…This integration also influences the friction on skin which can be an important aspect. We have shown that our in‐house‐produced POFs exhibit very low friction even compared to commercial textiles . Hence, contrary to bulky electronic components or glass optical fibres, they can be used on sensitive skin.…”
Section: Materials and Properties Of Pofmentioning
confidence: 93%
See 4 more Smart Citations
“…This integration also influences the friction on skin which can be an important aspect. We have shown that our in‐house‐produced POFs exhibit very low friction even compared to commercial textiles . Hence, contrary to bulky electronic components or glass optical fibres, they can be used on sensitive skin.…”
Section: Materials and Properties Of Pofmentioning
confidence: 93%
“…Here, we discuss recent, novel solutions in the area of wearable photonic fabrics, including research showing potential for further textile integration. Integration can be achieved in various ways; the most stable process is however the use of the sensor/treatment unit (the POFs) as yarn . Various methods such as knitting or weaving can be used as required by the application…”
Section: Solutions and Applicationsmentioning
confidence: 99%
See 3 more Smart Citations